Characteristics of thrombocytopenia, anasarca, fever, reticulin fibrosis and organomegaly syndrome: a retrospective study from a large Western cohort. (28th September 2021) - Maisonobe, Lucas; Bertinchamp, Rémi; Damian, Louise; Gérard, Laurence; Berisha, Mirlinda; Guillet, Stéphanie; Fieschi, Claire; Malphettes, Marion; Fadlallah, Jehane; Hié, Miguel; Dunogué, Bertrand; De Wilde, Virginie; et al.
Summary: Idiopathic multicentric Castleman disease (iMCD) is a non‐clonal inflammatory lymphoproliferative disorder of unknown origin. Recently, TAFRO syndrome (thrombocytopenia, anasarca, fever, reticulin fibrosis and organomegaly) emerged as a singular variant of iMCD in Asia and was associated with a severe course and a poor outcome. The present study describes the first large Western cohort of TAFRO syndrome patients ( n = 25) meeting the All Japan TAFRO Syndrome Research Group diagnostic criteria. Characteristics of TAFRO patients were compared to iMCD‐not otherwise specified (iMCD‐NOS) patients used as a control group ( n = 43). Our results show that despite baseline characteristics in accordance with previously reported series, Western TAFRO syndrome patients do not appear to present with a worse outcome than iMCD‐NOS patients. There were no significant differences between the two groups regarding treatment choice, response to rituximab (71% vs. 67%) or tocilizumab (69% vs. 91%) in TAFRO and iMCD‐NOS, respectively. The two‐year overall survival was above 95% in both groups. Limits of inclusion and exclusion criteria for TAFRO definition are also discussed. Our findings raise the question of the singularity of the TAFRO entity in Western countries. The data should promote further research using unsupervised models to identify markers of disease severity in Western cohorts of iMCD patients.